European League Against Rheumatism Sjögren's Syndrome Disease Activity Index and European League Against Rheumatism Sjögren's Syndrome Patient‐Reported Index: A Complete Picture of Primary Sjögren's Syndrome Patients. Issue 8 (26th July 2013) - Seror, R.; Gottenberg, J. E.; Devauchelle‐Pensec, V.; Dubost, J. J.; Le Guern, V.; Hayem, G.; Fauchais, A.‐L.; Goeb, V.; Hachulla, E.; Hatron, P. Y.; Larroche, C.; Morel, J.; et al.
<x xml:space="preserve">Abstract</x> Objective The European League Against Rheumatism (EULAR) Sjögren's Syndrome (SS) Disease Activity Index (ESSDAI) and the EULAR SS Patient‐Reported Index (ESSPRI) were recently developed. We aimed to determine whether patients' symptoms differed between patients with and without systemic involvement and if the disease‐specific indices correlated with each other in primary SS. Methods Fifteen French centers included 395 primary SS patients in the Assessment of Systemic Signs and Evolution in Sjögren's Syndrome Cohort. At enrollment, physicians completed the ESSDAI, the SS Disease Activity Index (SSDAI), and the Sjögren's Systemic Clinical Activity Index (SCAI), and patients completed the ESSPRI, the Sicca Symptoms Inventory, and the Profile of Fatigue and Discomfort. All scores were compared between patients with and without systemic involvement. Correlations between scores of systemic activity and patients' symptoms were obtained. Results At enrollment, 120 (30.4%) patients had never experienced systemic complication and 155 (39.2%) patients and 120 (30.4%) patients had, respectively, only past or current systemic manifestations. Past or current systemic patients had higher levels of symptoms, except dryness. The ESSDAI did not correlate with the patient‐scored ESSPRI (rho = 0.06, P = 0.30), whereas the SSDAI and the SCAI, which include subjective items, did correlate (rho = 0.28 and 0.25, respectively; P < 0.0001 for both). Conclusion Alterations of common patient‐reported outcomes are present in all patients with primary SS, including those with systemic complications. However, patient symptoms and systemic complications are 2 different facets of primary SS. Therefore, the use of both systemic and patients' indices, such as the ESSDAI and ESSPRI, are useful. Since these 2 facets weakly overlap, one should identify which of both components is the main target of the treatment to test, when designing clinical trials in primary SS.